2019
DOI: 10.1002/ange.201908256
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Self‐Assembly of Theta‐Shaped Colloids and Twinning of Their Crystal Phases

Abstract: Anisotropic colloids self‐assemble into different crystal structures compared to spherical colloids. Exploring and understanding their self‐assembly behavior could lead to creation of new materials with hierarchical structures through a bottom‐up process. Herein, we report metastable self‐assembly of theta‐shaped SiO2 colloids interacting with a depletion force in a quasi‐two‐dimensional space and we demonstrate that both a metastable “prone” crystal phase and a stable “standing” crystal phase can be formed, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In addition to rod-like particles, ellipsoidal particles with different chemical properties of the surface can also be assembled in richer structures of colloidal crystals by depletion attractions. Wang et al (Wang L. et al, 2019) synthesized columnar spherical silica particles with a PS girdle in the middle, as shown in Figure 4D, which have theta-shaped surface chemistry. When situated on a quasitwo-dimensional plane, these particles could form two types of ordered structures through depletion attraction.…”
Section: Preparation Of Colloidal Crystals By Depletion Attractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to rod-like particles, ellipsoidal particles with different chemical properties of the surface can also be assembled in richer structures of colloidal crystals by depletion attractions. Wang et al (Wang L. et al, 2019) synthesized columnar spherical silica particles with a PS girdle in the middle, as shown in Figure 4D, which have theta-shaped surface chemistry. When situated on a quasitwo-dimensional plane, these particles could form two types of ordered structures through depletion attraction.…”
Section: Preparation Of Colloidal Crystals By Depletion Attractionmentioning
confidence: 99%
“…FIGURE 4 (A) Schematic of overlapped excluded volumes of particles at different locations of the container; (B) Silica microspheres self-assemble into multilayer ordered structures at the air-water interface (Kim K. et al, 2019); (C) Schematic illustration showing the superlattices of TMV self-assembled in response to temperature and concentration (Li et al, 2013b); (D) Prone crystals and standing crystals self-assembled by θ-shape SiO 2 particles(Wang L. et al, 2019).…”
mentioning
confidence: 99%
“…Among this large variety of dendritic chemical structures, amphiphilic dendrimers, due to their well-defined architectures and shape persistence, have attracted considerable attention in the field of bottom-up hierarchical self-assembly for decades and found great applications in myriad fields, including supramolecular chemistry, gene transfection, drug delivery, and catalysis, to name but a few. [1][2][3][4][5][6][7][8][9][10] Unfortunately, a grand challenge to yield the delicate dendrimers requires tedious multistep reactions, purification processes, and stringent experimental conditions, which significantly limit the varieties and scopes of dendritic self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…[1,5] Fabrication of 2D and 3D CCs has attracted much interests. [2,[10][11][12][13] For example, randomly stacked hexagonal close packing is generally found in CCs formed by hard-sphere NPs, whereas soft CCs formed from polymeric NPs normally exhibit a face-centered cubic (fcc) structure. [2] Recent studies on assemblies of lead chalcogenide NPs also revealed the formation of hexagonal close-packed (hcp), body-centered cubic (bcc), and body-centered tetragonal (bct) superlattices.…”
mentioning
confidence: 99%